(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Communication can be as a sharing of meaning. Ethics, the right value given to that meaning and Culture, the means we use to share meaning. Earlier these were the products of our family and society. Their modes of transmission and interaction were the product of our need and our resources. Messages were often person to person, intimate, bound by local prejudices and customs. The mass media are a pervasive part of our life. Television occupies a major chunk of the ‘leisure’ time afforded by people all over the world and increasingly in India, has become an oft-quoted truism. But behind this common place assertion lies a host of issues - its long-term impact, particularly its role in the shaping of consciousness, its role as primary source of ‘values’, ‘culture’ and ‘leisure. Television’s impact on society is often analyzed in terms of its negative consequences, that is, lowering of moral standards, increase in our threshold violence, its role in promoting ethics of consumerism, individualism etc. The problem that crept in was the picturing of morally objectionable motion pictures appearing on television. There are two angles to analysis the role of mass communication. One, by taking the sociological perspective and look through a wide-lens and consider the functions performed by the mass media for the entire society, called macro analysis. Second, by looking through a close-up lens at the individual receivers of the content, the audience, and ask them how they use the mass media called micro-analysis. The heaviest period of television viewing by children is during prime time. It should be noted that many reruns are programmed during prime time. Thus, children see more programmes designed for adults than those developed for the younger generation. These viewing experiences expose them to commercials that express a powerful set of values. How to cite this article: Vasanth G. Impact of Digital Television on Audience Especially Children. J Adv Res Jour Mass Comm 2018; 5(4): 116-122. DOI: https://doi.org/10.24321/2395.3810.201828